The effectiveness of physiotherapist-delivered group education and exercise interventions to promote self-management for people with osteoarthritis and chronic low back pain: A rapid review Part I. Issue 2 (April 2015) - Toomey, Elaine; Currie-Murphy, Laura; Matthews, James; Hurley, Deirdre A.
Abstract: Background: Osteoarthritis (OA) and chronic low back pain (CLBP) are two of the most common and costly musculoskeletal conditions globally. Healthcare service demands mean that multiple condition group-based interventions are of increasing clinical interest, but no reviews have evaluated the effectiveness of group-based physiotherapy-led self-management interventions (GPSMI) for both conditions. Objectives: This rapid review aimed to evaluate the effectiveness of GPSMI for OA and CLBP. Design: Rapid reviews are an increasingly valid means of expediting knowledge dissemination and are particularly useful for addressing focused research questions. Method: The electronic databases MEDLINE, EMBASE, CINAHL, Cochrane Database of Systematic Reviews and Cochrane Register of Controlled Trials were searched. Structured group-based interventions that aimed to promote self-management delivered by health-care professionals (including at least one physiotherapist) involving adults' with OA and/or CLBP were included. The screening and selection of studies, data extraction and risk of bias assessment were conducted independently by two reviewers. Results: 22 Studies were found (10 OA, 12 CLBP). No significant difference was found between the effectiveness of GPSMI and individual physiotherapy or usual medical management for any outcome. Conclusions: GPSMI is as clinically effective as individual physiotherapy or usual medical management, but the best methods of measuring clinical effectiveness warrant further investigation. Further research is also needed to determine the cost-effectiveness of GPSMI and its implications.